2022 IEEE Energy Conversion Congress and Exposition (ECCE) 2022
DOI: 10.1109/ecce50734.2022.9947858
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Passive Observer-Based V/Hz Control for Synchronous Motors

Abstract: This paper proposes an observer-based volts-perhertz (V/Hz) control method for synchronous motors. The method is applicable to any synchronous motor type, from permanentmagnet (PM) motors to synchronous reluctance motors (SyRMs). The method consists of a state-feedback control law and a state observer, both of which are designed to be inherently sensorless. The gains can be selected using simple closed-form expressions, resulting in a locally stable and passive system in the whole feasible operating range. Uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…With positive design parameters α τ and α f , the mechanical impedance is passive in the feasible operating region where τ δ0 > 0. Consequently, the V/Hz control configuration is locally stable for any passive mechanics, as expected based on [22]. 4) Numerical Analysis of the Closed-Loop System: The closed-loop torque control is illustrated with a frequency response graph.…”
Section: Torque-control Loopmentioning
confidence: 67%
See 2 more Smart Citations
“…With positive design parameters α τ and α f , the mechanical impedance is passive in the feasible operating region where τ δ0 > 0. Consequently, the V/Hz control configuration is locally stable for any passive mechanics, as expected based on [22]. 4) Numerical Analysis of the Closed-Loop System: The closed-loop torque control is illustrated with a frequency response graph.…”
Section: Torque-control Loopmentioning
confidence: 67%
“…It can be shown that passivity condition for (22) with positive design parameters α τ , k p , and k i is…”
Section: Torque-control Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen to have the same inputs as the other PSC-based methods, despite the internal structure being different. It is based on a previously developed observer-based V/Hz control method and purposefully resembles it closely [6]. This is why terms such as virtual flux linkage and virtual torque are used even though they are not commonly used in the context of grid-connected converters, as explained in Chapter 2.4.…”
Section: Observer-based Power-synchronization Controlmentioning
confidence: 99%
“…This control method is named observer-based power-synchronization control (OPSC). OPSC is inspired by a previously developed observer-based V/Hz control method for synchronous machines [6]. The validity and performance of OPSC is assessed by means of linear analysis and simulations where OPSC will be compared to two other state-of-the-art PSC-based methods.…”
Section: Introductionmentioning
confidence: 99%